Perempuan Muda dan Partai Politik : Dari Descriptive Participation menuju Substantive Representation - Ani Widyani Soetjipto (Yayasan Jurnal Perempuan, 2023)
The low level of political participation among women in general, including young women, in Indonesia can be explained through three reasons. Firstly, women face a challenging playing field because politics is predominantly characterized by a masculine culture. Secondly, in their pursuit of political engagement, women encounter several obstacles, such as patriarchal structures, sexist and ageist views, and social class barriers. Thirdly, young women are also hindered by political nepotism, lack of party support, limited political knowledge, and financial constraints. This paper utilizes the conceptual framework of Women and Political Party by Lovenduski (1997), Squires (2007), Ann Phillips’ theory of women’s representation, as well as the works of Young, Mouffe, Childs, and Krook to examine the dynamics of young women and political parties in Indonesia from the 2019 elections to the upcoming 2024 elections. The focus is on the interconnection between descriptive participation and substantive representation. The research methodology employed involves a critical analysis of existing literature supplemented by interviews conducted with young women actively involved in five political parties qualified as participants in the 2024 elections (Golkar, NasDem, PKB, Demokrat, and PSI), including both ordinary party members and those who were elected as members of the DPR (People’s Representative Council of Indonesia) in the 2019 elections.